Management of Intramural Esophageal Dissection with Gastric Feeding Tube in an Alcoholic-hepatitis Patient - Ryoung Eun Ko; Won Sik Jung; Yoon Chae Lee; Sung Hoon Choi; Seung Young Seo (The Korean Journal of Gastroenterology, 2016)
Intramural esophageal dissection is a rare but clinically important condition in the field of gastroenterology. Classically, intramural esophageal dissection rarely occurs in patients who are anticoagulated or have poor medical condition, and its clinical presentation may include chest pain, dysphagia and hematemesis. Herein, we present a case of intramural esophageal dissection in an alcoholic hepatitis patient that was diagnosed by endoscopy and successfully treated with conservative management. (Korean J Gastroenterol 2016;67:35-38)